A Facile and Waste-Free Strategy to Fabricate Pt-C/TiO2 Microspheres: Enhanced Photocatalytic Performance for Hydrogen Evolution - Hui Li; Xiaoyan Zhang; Xiaoli Cui (International Journal of Photoenergy)
A facile and waste-free flame thermal synthesis method was developed for preparing Pt modified C/TiO2 microspheres (Pt-C/TiO2). The photocatalysts were characterized with X-ray diffraction, field emission scanning electron microscopy, transmission electron microscope, ultraviolet-visible (UV-vis) diffuse reflectance spectra, X-ray photoelectron spectroscopy, and thermogravimetry analysis. The photocatalytic activity was evaluated by hydrogen evolution from water splitting under UV-vis light illumination. Benefitting from the electron-hole separation behavior and reduced overpotential of H+/H2, remarkably enhanced hydrogen production was demonstrated and the photocatalytic hydrogen generation from 0.4 wt% Pt-C/TiO2 increased by 22 times. This study also demonstrates that the novel and facile method is highly attractive, due to its easy operation, requiring no post treatment and energy-saving features.